Finite element analysis of the total forming force of thin-walled metallic tube junctions employing elastomers - Foli, Cristiano Roberto Martins (2012)
Among the forming processes can be emphasized the metallic junction forming using elastomers. This forming process presents a considerable number of variables, as for instance: the definition of the necessary relationship between the progress of the dome formed and the developed pressure in the elastomer, the friction and lubricating conditions during the junction forming, the role of the anisotropy and the material strain-hardening, as well as the influence of the strain-rate in the forming process and the definition of the maximum force to form the junctions. Process modelling has become an effective tool in reducing the lead-time and the cost for designing forming processes for manufacturing automotive and aerospace components. Several research works are being developed seeking to approximate the experimental and mathematical analysis in manufacturing processes. Computer software’s for process modelling, and the transfer of this technology to the industry have contributed towards the development of this tool. This chapter aims to calculate the total forming force through numerical simulation process of thin-walled tube junctions using an elastômero, where important parameters are considered such as: friction, elastomer length and material mechanical properties. Furthermore, in the work the finite element program Deform 3D is employed. Hence, comparisons are made between the obtained numerical results and available experimental results.